O uso da CIF como instrumento de avaliação pelos terapeutas ocupacionais em pesquisas no Brasil: uma revisão integrativa da literatura - ANDRADE, Isabelle dos Santos (2023)
Occupational therapists are professionals empowered to evaluate all aspects of the domain, its interrelations, and the client in their contexts and environments. The occupational therapist can use several instruments for their evaluation and data collection, among which the International Classification of Impairments, Disabilities and Handicaps (ICIDH) can be used as a research tool in their work. The present study aimed to perform an integrative review on the use of ICI as an instrument for collecting data by Occupational Therapists in Brazilian research. An online survey was conducted in the databases: Virtual Health Library (VHL) and Scientific Electronic Library Online (SCIELO) and after the analyzes, it was identified that only two articles used the ICI to collect data. It was possible to verify that the ICI was sensitive in evaluating and identifying problems related to the activities of daily living and social participation of the individuals who participated in the research. In relation to the common results found in Articles A and B, it was observed that the ICI made it possible to register and evaluate the results in a standardized way, as well as to be able to establish the understanding of the domains referring to ADLs and IADLs that were classified as impaired and how they affect people's activities and participation. After the integrative review, it was inferred that the ICI makes it possible to understand the impact of different pathologies on subjects' occupations even in different age groups.